Pregnancy-Associated Plasma Protein A, Free β-hCG, Nuchal Translucency, and Risk of Pregnancy Loss - Goetzl, Laura; Krantz, David; Simpson, Joe Leigh; Silver, Richard K.; Zachary, Julia M.; Pergament, Eugene; Platt, Lawrence D.; Mahoney, Maurice J.; Wapner, Ronald J. (Obstetrics and gynecology (New York. 1953), 2004)
To estimate the likelihood of clinical early and late pregnancy loss as a function of first-trimester maternal serum analytes and fetal nuchal translucency measurements. Study subjects were recruited for a National Institute of Child Health and Human Development-sponsored multicenter cohort study initially designed to study the detection of Down syndrome during the first trimester of pregnancy. The cohort consisted of women who had a live fetus between 10 and 14 weeks of gestation and had no significant vaginal bleeding. Women with prior fetal trisomy (T21/18) and those with structural or chromosomal abnormalities in the index pregnancy were excluded. First-trimester screening consisted of pregnancy-associated plasma protein A (PAPP-A), free beta-hCG, and nuchal translucency. Pregnancy loss rates in women with various levels of PAPP-A, free beta-hCG, or nuchal translucency (less than 1st, less than 5th, more than 95th, and more than 99th percentile) were compared with losses in women with normal values (5th to 95th percentile). The mean gestational age at screening of 7,932 women meeting study criteria was 12.1 weeks. Loss rates were only 0.36% at less than 20 weeks after normal free beta-hCG, PAPP-A, and nuchal translucency. Conversely, low levels of PAPP-A and free beta-hCG as well as increased nuchal translucency were individually associated with increased early loss. These associations persisted after controlling for maternal age and race using logistic regression analysis. Normal values of PAPP-A, free beta-hCG, and nuchal translucency are associated with a very low risk of pregnancy loss at less than 20 weeks.